Analisis Efektivitas dan Efisiensi Pagu Anggaran Terhadap Realisasi Anggaran Pendapatan dan Belanja Daerah (APBD Pemerintah Daerah Kabupaten / Kota di Provinsi Jawa Barat Tahun 2020 - 2021 - Febrianti, Rita (Program Studi Sistem Informasi Akuntansi Kampus Kota Sukabumi, 2024)
This research is motivated by the importance of the level of social welfare, so that realizing economic prosperity for the people is one of the main objectives of the establishment of the Unitary State of the Republic of Indonesia (NKRI). The problem formulation in this research is to determine the level of effectiveness and efficiency of financial performance of the City/Regency Regional Government in West Java Province during the Covid-19 pandemic. This research uses quantitative methods, the data used is secondary data, namely the budget ceiling and APBD budget realization reports obtained from the official DJPK (Directorate General of Financial Balance) website. The data analysis method used is the effectiveness comparison ratio method and the efficiency comparison ratio method. Based on research results, the average value of the financial performance effectiveness of City/Regency Regional Governments in West Java Province during the Covid-19 Pandemic was 106% with very effective criteria. Meanwhile, the average value of financial performance efficiency of City/Regency Regional Governments in West Java Province during the Covid-19 Pandemic was 99% with the criteria being less efficient.